New polymorphic microsatellite markers able to distinguish among Candida parapsilosis sensu stricto isolates - Sabino, Raquel (2011)
Among the Candida species causing bloodstream infections, Candida parapsilosis is one of the most frequently isolated. The objective of the present work was the identification of new microsatellite loci able to distinguish among C. parapsilosis isolates. DNA sequences with trinucleotide repeats were selected from the C. parapsilosis genome database. PCR primer sets flanking the microsatellite repeats were designed and tested with 20 independent isolates. On the basis of the amplification efficiency, specificity, and observed polymorphism, four of the sequences were selected for strain typing. Two hundred thirty-three independent C. parapsilosis sensu stricto isolates were genotyped by using these markers. The polymorphic loci exhibited from 20 to 42 alleles and 39 to 92 genotypes. In a multiplex analysis, 192 genotypes were obtained and the combined discriminatory power of the four microsatellites was 0.99. Reproducibility was demonstrated by submission of subcultures of 4 isolates each, in triplicate, interspersed with unique numbers among a group of 30 isolates for blind testing. Comparison of the genotypes obtained by microsatellite analysis and those obtained by randomly amplified polymorphic DNA analysis, restriction fragment length polymorphism analysis, and internal transcribed sequence grouping was performed and showed that the microsatellite method could distinguish individual isolates; none of the other methods could do that. Related species, C. orthopsilosis and C. metapsilosis, were not confused with C. parapsilosis sensu stricto. These new microsatellites are a valuable tool for use for the differentiation of C. parapsilosis sensu stricto strains, vital in epidemiology to answer questions of strain relatedness and determine pathways of transmission.